PERANCANGAN SEMI GANTRY CRANE KAPASITAS 10 TON DENGAN BANTUAN SOFTWARE - Joseph Rama Wiratama; G Soeharsono (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Indonesia which is an archipelago country has a lot of harbour for conveying and delivering goods which is stored in container from one island to another island. Containers are very heavy so that required a strong and stable lifting machine, also have a good performance and safety. Semi gantry crane as one of the example of lifting machine is designed using assistance of software for that purpose.